Numerical study and safety spacing of buried parallel gas pipelines: A study based on TNT equivalent method. (December 2018) - Guo, Yanbao; Liu, Chengcheng; Wang, Deguo; He, Renyang
Abstract: In order to save land resources for pipeline construction and reduce maintenance costs, a method of parallel laying pipeline has been adopted. The safety spacing was the primary problem to ensure the security of pipeline laying and operating. A numerical simulation method of buried parallel gas pipelines leakage-induced explosion based on TNT equivalent was presented. According to the combustible gas explosion theory, the damage law of shock waves impact on the parallel pipeline was analyzed. The maximum displacement with different parallel space and different thickness were simulated and discussed. Ultimately, the degree of risk of buried pipelines parallel spacing was analyzed and the safety spacing was determined. It provided guidance for the construction and operation of buried parallel gas pipelines. Highlights: Numerical simulation of buried parallel natural gas pipeline explosive was carried out based on TNT equivalent method. The fracture failure position was perpendicular to the maximum deformation position when the distance was less than 3 m. The maximum deformation position was gradually transferred to the top of pipeline coinciding with fracture failure position. The safety distance between two buried parallel pipelines was more than 8 m for pipeline thickness 22 mm.